Teaching the subject of literary reading in primary schools with the integration of the subjects of kyrgyz and english languages (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Modern education places great emphasis on interdisciplinary integration, which plays a key role in developing holistic knowledge and skills among primary school students. The aim of the research is to substantiate the theoretical foundations of an integrated lesson system in Kyrgyz language and Kyrgyz literature, as well as to develop methods for using literary texts and integrated teaching techniques to foster communicative skills in young learners. The article explores technologies used in the analysis of literary works during subject integration in primary education. Practical examples of implementing the concept of integrated learning of the Kyrgyz literature with Kyrgyz and English language subjects also provided.
Keywords: subject integration, innovative technologies, effective learning, student motivation, interactive education, literary analysis, primary school